Antihepatotoxic effect of isolated chitin from Rhizopus oryzae against paracetamol-induced hepatotoxicity - Akila Ramanathan; Ramya Kittusamy (Bangladesh Pharmacological Society, 2011)
The present study was aimed at investigating the antihepatotoxic activity of isolated fungal chitin, a natural polysaccharide from Rhizopus oryzae NCIM1009 against paracetamol-induced toxicity in rats. Changes in the levels of biochemical markers of hepatic injury such as  serum glutamate oxaloacetic transaminase (SGOT), serum glutamic pyuruvic transaminase (SGPT), alkaline phosphatase, bilirubin and total protein were determined in both treated and control group of rats. The effect of fungal chitin was compared with that of silymarin (25 mg/kg). The results showed that paracetamol (750 mg/kg) elevated the levels of biomarkers enzymes. Treatment with fungal chitin (200 mg/kg) brought the marker level near to normal and showed significant hepatoprotective activity. Acute toxicity studies of fungal chitin was carried out and found safe up to 2,000 mg/kg. The isolated fungal chitin was characterized by IR spectroscopy and compared with commercial chitin.